Towards an African Economic Community : reflections on the role of the OAU, AfDB and UN/ECA in the implementation of the Abuja Treaty. - MWASE, Ngila (1997)
Calls for close interaction between continental, regional and country level organs in the design and implementation of programs, including a central role for the private sector in facilitating the integration of African economies.